A randomized study of cognitive remediation for forensic and mental health patients with schizophrenia - Ahmed, Anthony O.; Hunter, Kristin M.; Goodrum, Nada M.; Batten, Nancy-Jane; Birgenheir, Denis; Hardison, Erik; Dixon, Thaddeus; Buckley, Peter F. (Journal of psychiatric research, 2015)
Cognitive remediation has proven efficacy for improving neurocognition in people with schizophrenia. The current study evaluated the benefits of cognitive remediation on neurocognition, functioning, psychotic symptoms, and aggression in a sample of forensic and mental health patients. Care recipients with schizophrenia or schizoaffective disorder (N = 78) receiving services in the forensic and mental health units of a state hospital were randomized to participate in cognitive remediation versus computer games control activities. Participants' neurocognition, functional capacity, experiential recovery, psychotic symptoms, and aggression incidents were assessed at baseline and posttreatment. Cognitive remediation was associated with improvements in several neurocognitive domains and circumscribed domains of functional capacity. People assigned to cognitive remediation experiences greater reductions in negative symptoms, agitation/excitement, and verbal and physical aggression. In addition to improving neurocognition in long-term hospitalized forensic and mental health patients, cognitive remediation may enhance efforts at reducing negative symptoms, emotion dysregulation, and aggression incidents. Forensic settings may represent a new frontier for the clinical dissemination of cognitive remediation. •Impairments in working memory and verbal learning are more profound among offenders with schizophrenia than non-offenders.•Cognitive remediation contributes to improvements in neurocognition and circumscribed domains of functional competence.•Cognitive remediation contributes secondarily to decreased negative symptoms, excitement/agitation, and aggression.